Ethicality and imagination : on luminous abodes - Sallis, John, 1938- (Sallis, John, 1938- Works., 2022)
"Ethicality and Imagination" is the astounding conclusion to John Sallis's landmark trilogy launched with "Force of Imagination" and "Logic of Imagination". In this new work, Sallis embarks on an unforgettable voyage spanning the cosmos and delving deep into what makes us human. If the first two works consider the question of being and thinking, respectively, the third and culminating volume takes up the question of action. In a series of highly original and always provocative meditations, Sallis articulates the way humans are rooted in their abodes yet not determined by them. "Ethicality and Imagination" develops a new approach to the relation of the imagination to literature, ethics, political thought, and recent discoveries in astrophysics. It represents a brilliant conclusion to one of the most exciting works of thinking in the Continental school in recent decades.